Soft robotics : trends, applications and challenges : proceedings of the Soft Robotics Week, April 25-30, 2016, Livorno, Italy /: trends, applications and challenges : proceedings of the Soft Robotics Week, April 25-30, 2016, Livorno, Italy. ([2017]) - Unknown
No abstract available